Comparing the route-choice behavior of pedestrians around obstacles in a virtual experiment and a field study. (October 2019) - Li, Hongliu; Zhang, Jun; Xia, Long; Song, Weiguo; Bode, Nikolai W.F.
Highlights: We analyze pedestrian route choice behavior around obstacles in a simple scenario. We compare a field study and a virtual experiment with identical setups. We find qualitatively similar results in both settings. This helps to validate virtual experiments as a useful methodology. Abstract: Pedestrians often need to decide between different routes they can use to reach their intended destinations, both during emergencies and in their daily lives. This route-choice behavior is important in determining traffic management, evacuation efficiency and building design. Here, we use field observations and a virtual experiment to study the route choice behavior of pedestrians around obstacles delimiting exit routes and examine the influence of three factors, namely the local distance to route starting points and the pedestrian density and walking speeds along routes. Crucially, both field study and virtual experiment consider the same scenario which allows us to directly assess the validity of testing pedestrian behavior in virtual environments. We find that in both data sets the proportion of people who choose a closer exit route increases as the difference in distance between exit route starting points increases. Pedestrians' choices in our data also depend on pedestrian density along routes, with people preferring less used routes. Our results thus confirm previously established route choice mechanisms and we can predict over 74% of choices based on these factors. The qualitative agreement in results between the field study and the virtual experiment suggests that in simple route-choice scenarios, such as the one we investigate here, virtual experiments can be a valid experimental technique for studying pedestrian behavior. We therefore provide much-needed empirical support for the emerging paradigm of experiments in virtual environments.